Apparel Retail Outlet Selection: Influence of Service Levels in Goa - Gupta, Mathala Juliet; Hiremath, Chetan V. (Indian Journal of Marketing, 2011)
A Retailer is one who makes products and services available to end consumers. The Retail industry is witnessing many challenges like soaring realty prices and high inflation rate, which have made many retail formats unprofitable and reduced the customer’s confidence in the economy, thereby, resulting in lower sales. Our Government’s unwillingness to allow more inflow of FDI in retail has made the situation more challenging for the existing players. Technology has blurred the demarcation between suppliers and retailers. The real challenge for the retailers is to balance customer expectations, and the fixed costs. There are many theories put forth by scholars to explain evolution of retail formats. A survey was conducted in three major cities of Goa. All the 400 respondents were aged between 18yrs to 33yrs. The role of merchandise quality, variety, style, brand, service and prices offered by a particular type of outlet was studied. Also, service factors like ambience, parking space, personal assistance, sitting lounge, loyalty program and home delivery in the choice of retail outlets by shoppers across the three major cities of Goa was studied. Kendall’s coefficient of concordance was used to test the findings.